2010
DOI: 10.1007/s10903-010-9402-0
|View full text |Cite
|
Sign up to set email alerts
|

Binge Drinking Among Male Mexican Immigrants in Rural North Carolina

Abstract: While it is clear that alcohol use among immigrants from Mexico has serious consequences, limited data exist on the correlates of this behavior for Mexican immigrants residing in rural, traditionally non-Hispanic settings. A cross-sectional survey with an outreach approach was used to target 173 male Mexican immigrants in rural eastern North Carolina. Questionnaires including demographics, pre and post immigration alcohol use, acculturation, stress, social support, and depressive symptoms were administered thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 23 publications
1
12
0
Order By: Relevance
“…In a separate Latino sample taken in North Carolina of Latino men who have sex with men, the TWD prevalence was 17.4% and the HED was 30.0% (Rhodes et al, 2012), both lower than observed in this analysis. In a small cross-sectional survey of North Carolina Latino men, 48% of the sample reported binge drinking, which is closer to the 53% observed in this study (Loury et al, 2011). In multivariable modeling, TWD was associated with affiliation with a religion/denomination that does not have a prohibition against drinking alcohol.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…In a separate Latino sample taken in North Carolina of Latino men who have sex with men, the TWD prevalence was 17.4% and the HED was 30.0% (Rhodes et al, 2012), both lower than observed in this analysis. In a small cross-sectional survey of North Carolina Latino men, 48% of the sample reported binge drinking, which is closer to the 53% observed in this study (Loury et al, 2011). In multivariable modeling, TWD was associated with affiliation with a religion/denomination that does not have a prohibition against drinking alcohol.…”
Section: Discussionsupporting
confidence: 82%
“…However, among Latinos, little research has been conducted on the role of stress in predicting drinking behavior. The Hispanic American Baseline Alcohol Study (HABLAS) identified a link between increased discriminative stress and increased drinking (Vaeth et al, 2012), and Loury, Jesse, and Wu (2011) found that Mexican immigrant men who reported HED also reported lower levels of perceived social support. However, the perception of discrimination tends to differ by immigrant generation; first-generation Latinos tend to perceive less discrimination than do second-generation Latinos (Viruell-Fuentes & Schulz, 2009; Viruell-Fuentes, 2007).…”
Section: Psychosocial Predictors Of Heavy Drinking Among Latino Menmentioning
confidence: 99%
“…In contrast, recent studies of immigrant Latino men in North Carolina found that non-drinkers accounted for only 26% and 37% of participants (Grzywacz et al, 2007; Loury et al, 2011). As those studies presumed heterosexuality (i.e., did not assess sexual orientation), their findings may not be directly comparable to our sample.…”
Section: Discussionmentioning
confidence: 72%
“…Recent research in North Carolina found high levels of binge drinking among Latino men (Grzywacz, Quandt, Isom, & Arcury, 2007; Kim-Godwin & Fox, 2009), which was associated with Spanish language use and inversely associated with age and social support (Loury, Jesse, & Wu, 2011; Ornelas, Eng, & Perreira, 2011). These findings suggest a pattern of prevalent risky drinking that is driven by social stressors.…”
Section: Introductionmentioning
confidence: 99%
“…Also, undocumented immigrants may find it more difficult to hide in rural areas, which have greater socio and spatial visibility. Studies have demonstrated that members of excluded groups have difficulty navigating rural public spaces without feeling stigmatized, which over time can impact their mental wellbeing (Loury, Jesse, & Wu, 2011; Mora et al, 2013). …”
Section: Discussionmentioning
confidence: 99%